1989
DOI: 10.1083/jcb.108.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and exchange of intermediate filament proteins of neurons: neurofilaments are dynamic structures.

Abstract: Abstract. We have explored the dynamics of intermediate filament assembly and subunit exchange using fluorescently labeled neurofilament proteins and a fluorescence resonance energy transfer assay. Neurofilaments (NFs) are assembled from three highly phosphorylated proteins with molecular masses of 180 (NF-H), 130 (NF-M), and 66 kD (NF-L) of which NF-L forms the structural core. The core component, NF-L, was stoichiometrically labeled at cysteine 321 with fluorescein, coumarin, or biotin-maleimide to produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…Otherwise, it might play a role in axonal transport of NF. NF have been shown in in vitro studies to be more dynamic structures than previously thought (Angelides et al, 1989). Further recent fluorescent photobleach-recovery and biotin immunocytochemistry studies indicated directly that NF in the axons turned over within small area of the axoplasm, possibly by the mechanism of lateral and segmental incorporation of new subunits.…”
Section: Discussionmentioning
confidence: 93%
“…Otherwise, it might play a role in axonal transport of NF. NF have been shown in in vitro studies to be more dynamic structures than previously thought (Angelides et al, 1989). Further recent fluorescent photobleach-recovery and biotin immunocytochemistry studies indicated directly that NF in the axons turned over within small area of the axoplasm, possibly by the mechanism of lateral and segmental incorporation of new subunits.…”
Section: Discussionmentioning
confidence: 93%
“…However, it also seemed certain that only 1 mol of phosphorylation could disrupt the integrity of the filaments. Angelides et al (1989) described in their recent paper that phosphorylated NF-L could not assemble but that phosphorylation of NF-L filaments appeared to stabilize them. The second of their observation is in contradiction with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by increasing phosphorylation locally, myelination might encourage local retention of neurofilaments as part of the stationary cytoskeleton. A final possibility is that myelination encourages local assembly of neurofilaments from subunits and precursors (Angelides et al, 1989;Okabe et al, 1993). In any event, although demyelination reverses the phosphorylation of neurofilaments in the underlying axons, it has a lesser effect on neurofilament number (de Waegh et al, 1992).…”
Section: Effects Of Myelination On Neurojilament Numbermentioning
confidence: 99%